Unbalanced translocation der(11)t(11;12)(q23;q13): a new recurrent cytogenetic aberration in myelodysplastic syndrome with a complex karyotype - Yamamoto, Katsuya; Hato, Akio; Minagawa, Kentaro; Yakushijin, Kimikazu; Urahama, Norinaga; Gomyo, Hiroshi; Sada, Akiko; Okamura, Atsuo; Ito, Mitsuhiro; Matsui, Toshimitsu (Cancer genetics and cytogenetics, 2004)
Cytogenetic abnormalities are observed in approximately one half of cases of myelodysplastic syndrome (MDS). Partial or complete chromosome losses and chromosome gains are frequently found, but there is a relatively high incidence of unbalanced translocations in MDS. We describe here two cases of MDS with an unbalanced translocation, der(11)t(11;12)(q23;q13). Both patients were 69 years of age and diagnosed with refractory anemia with excess of blasts in transformation (RAEB-t) according to the high percentage of blasts in the peripheral blood. Cytoplasmic hypogranulation of neutrophils was evident as a dysplastic change. The blasts were positive for CD4 and CD41a as well as CD13, CD33, CD34 and HLA-DR in both cases. Chromosome analysis showed complex karyotypes including a der(11)t(1;11)(q11;p15)t(11;12)(q23;q13) in case 1 and der(11)t(11;12)(q23;q13) in case 2 plus several marker chromosomes. Spectral karyotyping confirmed the der(11)t(11; 12)(q23;q13) and clarified the origin of marker chromosomes, resulting in del(5q) and del(7q). Fluorescence in situ hybridization (FISH) analyses with a probe for the MLL gene demonstrated that the breakpoints at 11q23 were telomeric to the MLL gene in both cases. FISH also showed that the breakpoint at 11p15 of the case 1 was telomeric to the NUP98 gene. Considering another reported case, our results indicate that the der(11)t(11;12)(q23;q13) is a recurrent cytogenetic abnormality and may be involved in the pathogenesis of advanced-stage MDS.